Constructions of partial geometric difference sets from spread-like partitions - Piri, Semih; Olmez, Oktay (National Library of Serbia, 2025)
Partial geometric difference sets (PGDSs) were introduced by O. Olmez. In this paper, we construct partial geometric difference sets by using spread-like constructions method. We also give some PGDS constructions by using cosets of a finite group. We call it partial coset construction methods.